Fusion research in stellarator department of IPP NSC KIPT - Moiseenko, V.Е.; Dreval, M.B.; Kovtun, Yu.V.; Kulyk, Yu.S.; Glazunov, G.P.; Kazakov, Ye.O.; Ongena, J.; Sharapov, S.E.; Thomsen, H.; Garkusha, I.E. (Problems of Atomic Science and Technology, 2022)
This paper briefly describes intrinsic and collaborative scientific activities in the Stellarator Department of the Institute of Plasma Physics of the National Science Center “Kharkov Institute of Physics and Technology” in last two years. These activities include experiments on JET tokamak, stellarators Wendelstein 7-X and Uragan-2M, TOMAS toroidal device and theoretical studies related to modeling of radio-frequency fields in plasma and conceptual development of the stellarator-mirror fission-fusion hybrid. Hаведено короткий опис власної наукової діяльності та діяльності у колаборації відділу стелараторів Інституту фізики плазми ННЦ “Харківський фізико-технічний інститут” за останні два роки. Уся діяльність включає експерименти на токамаку JET, стелараторах Wendelstein 7-X та Ураган-2М, тороїдальному пристрої TOMAS і теоретичні дослідження, пов’язані з моделюванням високочастотних полів у плазмі та концептуальною розробкою ядерно-термоядерного гібриду на базі стеларатора з вбудованою відкритою пасткою.